2021
DOI: 10.3390/jcm10194600
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Value of a Protective Proximal Humeral Cerclage in Reverse Total Shoulder Arthroplasty

Abstract: Reverse shoulder arthroplasty (RSA) is a commonly performed salvage procedure for failed proximal humeral fracture fixation. The rate of intraoperative periprosthetic fractures is higher compared to primary RSA. The goal of this study was to investigate the biomechanical value of a protective cerclage during stem impaction in a revision surgery setting. Twenty-eight fresh-frozen human humeri were used to assess different configurations for steel wire and FiberTape cerclages. A custom-built biomechanical test s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In a case series on patients undergoing RTSA for degenerative diseases, Kriechling et al managed intraoperative nondisplaced calcar fracture with either suture or metal cerclage achieving fracture healing without any sign of stem subsidence or loosening [ 34 ]. Moreover, as shown with a biomechanical study, the protection of the metaphyseal calcar region with steel wire cerclage results in an increased energy needed to make the fracture progress distally to the cerclage [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a case series on patients undergoing RTSA for degenerative diseases, Kriechling et al managed intraoperative nondisplaced calcar fracture with either suture or metal cerclage achieving fracture healing without any sign of stem subsidence or loosening [ 34 ]. Moreover, as shown with a biomechanical study, the protection of the metaphyseal calcar region with steel wire cerclage results in an increased energy needed to make the fracture progress distally to the cerclage [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the increasing need for the strengthening support of the cerclage constructs mainly relies on the aging patient population with increasing numbers of periprosthetic fractures as one major indication [ 5 , 9 ]. Furthermore, cerclages are nowadays not only used for fracture treatment but may also provide a protective character for primary arthroplasty implantation, especially in patients with reduced bone quality [ 10 , 11 ]. Lastly, the application of cerclage constructs can help to manage reduction and serve as primary stabilization for complex fractures, outlining the variety of indications [ 12 ].…”
Section: Discussionmentioning
confidence: 99%